Ideological basis in the formation of the Shiromani Gurdwara Prabandhak Committee and the Shiromani Akali Dal: exploring the concept of Guru-Panth. (3rd April 2021) - Singh, Pashaura
ABSTRACT: This article explores the ideological foundations in the formation of the Shiromani Gurdwara Prabandhak Committee (SGPC) and Shiromani Akali Dal (SAD). It begins with the examination of the process of institutionalization from the Kartarpur period to modern times, focusing on the centrality of sacred space in Sikh corporate life. The overall structure, organization, and the underlying arguments of this essay revolve around the evolution of the doctrine of Guru-Panth, referring to two meanings: one, 'the Panth of the Guru, ' refers to the Sikh community; the other, 'the Panth as the Guru, ' referring to the Guru-Panth doctrine, which developed from the earlier idea that the Guru is mystically present in the congregation (saṅgat).